Russia's foreign security policy in the 21st century Putin, Medvedev and beyond - Haas, Marcel de (Contemporary security studies, 2010)
This book examines Russia's external security policy under the presidencies of Vladimir Putin, Dmitry Medvedev and beyond. The Russian Federation has developed from a neglected regional power into a self-declared resurgent superpower. Russia's background in the former Soviet Union as well as close ties with the upcoming new powers of China and India served as spring-boards towards regaining an influential status in the world. Simultaneously, Moscow developed an assertive policy towards the West and unwilling neighbours, culminating in August 2008 in an armed conflict with Georgia. Reviewing this decade of Russian international security policy, this work analyses security documents, military reforms and policy actions towards friends and foes, such as the USA and NATO, to provide an assessment of the future security stance of the Kremlin. This book will be of much interest to students of Russian politics and foreign policy, European politics and Security Studies and IR in general.